Pengembangan Aplikasi Kasir pada Rumah Makan Bahari Menggunakan Model Waterfall - Yulianti, Yulianti; Pangihutan, Nicolas Josua; Bashari, Ridwan; Ariadi, Seno; Mulyati, Sri (Jurnal Teknologi Sistem Informasi dan Aplikasi, 2022)
The research was conducted to find out the cashier service at the Bahari Restaurant which still uses the system manually when inputting data, this can be said to be less effective and efficient, due to frequent errors in calculating the amount to be paid and it takes a lot of time needed, because it still uses In the manual way, the archive of the transaction only has one copy, causing difficulty in finding data when recapitulating sales data, therefore with the cashier system at Bahari's restaurant it can be expected to simplify the calculation of the transaction process carried out and minimize the occurrence of errors that occur in the manufacture of receipts or proof of payment.